The importance of evolutionary history in studies of plant physiological ecology : examples from cerrados and forests of central Brazil - Hoffmann, William Arthur (2008)
Studies that compare physiology, anatomy, and ecology across species have offered some of the best insight into adaptation and evolutionary constraints in plants. As a result, the comparative approach has become increasingly used in studies of plant physiological ecology. The high species diversity of Brazilian biomes provides many excellent opportunities for comparative plant ecophysiology, and could be better exploited for understanding the evolution of plant form and function. In this paper we emphasize the importance of considering phylogenetic information for the design and analysis of comparative studies, relying on examples from comparisons of woody plants from cerrado and gallery (riparian) forests. The use of congeneric species pairs, each containing one cerrado species and one forest species of the same genus, greatly improves statistical power while assuring phylogenetic independence, an essential condition for inference in comparative studies. For example, in a study of seedlings of nine cerrado species and nine forest species, when we ignore phylogenetic relationships, it is not be possible to conclude that cerrado and forest species differ with regard to leaf area ratio (LAR), specific leaf area (SLA), or seedling height. If, however, we use the generic groupings to account for phylogenetic effects, then we find that seedlings of savanna species have lower LAR, SLA, and seedling height. Much of the phylogenetic inertia observed for these traits appears related to the fact that these traits are all strongly correlated with seed mass, which has been previously shown to be strongly conserved phylogenetically. These examples emphasize the importance of phylogenetic information in comparative studies. _________________________________________________________________________________ ABSTRACT